Stem Cells and Cellular Origins of Breast Cancer: Updates in the Rationale, Controversies, and Therapeutic Implications - Zhou, Jiaojiao; Chen, Qishan; Zou, Yiheng; Chen, Huihui; Qi, Lina; Chen, Yiding (Frontiers in Oncology, 2019)
Breast cancer stem cells have been known to contribute immensely to the carcinogenesis of the breast and therapeutic resistance in the clinic. Current studies show that breast cancer stem cell population is heterogeneous with various cellular markers and regulatory signaling pathways. Even different subtypes of breast cancer have distinct BCSC subtypes and frequencies. In this review, we provide an overview of the characteristics of breast cancer stem cells, including the various molecular markers, the prominent regulatory signaling and complex microenvironment. The cellular origins of breast cancer are discussed to understand the stem cell heterogeneity and their diverse differentiations. Importantly, we also outline the recent advances and controversies in the therapeutic implications of breast cancer stem cells in different breast cancer subtypes.